Triglyceride-glucose index and cancer risk: a prospective cohort study in Taiwan - Hsiao-Yun Yeh; Mei-Hung Pan; Chih-Jen Huang; Shiao-Ya Hong; Hwai-I Yang; Ying-Ying Yang; Chia-Chang Huang; Hung-Cheng Tsai; Tzu-Hao Li; Chien-Wei Su; Ming-Chih Hou (Diabetology & Metabolic Syndrome)
Abstract Background Insulin resistance (IR) is a key metabolic abnormality associated with adverse health outcomes, including increased cancer risk. The triglyceride-glucose (TyG) index, a validated surrogate marker of IR, has been linked to metabolic dysfunction; however, its association with cancer risk in large population-based cohorts remains unclear. This study aimed to evaluate the relationship between TyG index and cancer risk in Taiwanese population. Methods We analyzed 150,592 participants from the Taiwan Biobank, among whom 148,809 were linked to the Taiwan Cancer Registry (2011–2022) for cancer incidence tracking. Cancer risk was assessed across TyG quartiles over a median follow-up of 5.7 years (IQR: 3.4–7.6). Hazard ratios (HRs) and 95% confidence intervals (CIs) were estimated using Cox proportional hazards models, adjusting for key covariates. Results Higher TyG index levels were associated with increased risks of digestive system cancer (adjusted HR [aHR]: 1.17, 95% CI: 1.05–1.29), colorectal cancer (aHR: 1.25, 95% CI: 1.08–1.44), and urinary tract cancer (aHR: 1.47, 95% CI: 1.18–1.85). While subgroup trends suggested numerically higher risks in males, individuals aged ≥ 50 years, and those with overweight or obesity for these cancer types, formal interaction tests did not support statistically significant effect modification in these groups. Significant interactions were observed for overall cancers by age (P < 0.001) and BMI (P = 0.012), and for urinary tract cancer by drinking status (P = 0.047). In a subset of 19,808 participants with follow-up data, higher TyG quartiles were also linked to fatty liver, carotid plaques, and persistent IR over time (r = 0.75). Conclusions Higher TyG index levels, indicative of greater IR, are associated with an elevated risk of digestive system, colorectal, and urinary tract cancers. Evaluating TyG index levels could assist in risk stratification for these cancers among individuals with persistent IR, supporting targeted prevention strategies.